Standar Prosedur Operasional Terhadap Resiko Jatuh Pasien Di Ruang Rawat Inap di Puskesmas - Naka, Ali Syahid Bayau; Mustari, Sahdan; Syafri, Muhammad; Jauharuddin, Arfiah (Barongko: Jurnal Ilmu Kesehatan, 2023)
Hospital patient safety is a system by which hospitals make patient care safer. This system includes risk assessment, identification and management of matters related to patient risk, patient reporting and analysis, the ability to learn from incidents and follow up as well as implementing solutions to minimize the occurrence of risks. Objective: to determine the relationship between nurses' knowledge in implementing Standard Operational Procedures and the risk of falls in patients in the Puskesmas Inpatient Room. The research method used in this research is quantitative with an analytical survey research design using a cross sectional approach, namely the type of research for each research subject is only once and measurements are made on the subject's character status or variables at the time of examination. This research was carried out at one of the community health centers in Makassar. Results: Based on the results of the analysis, univariate analysis has been carried out on each variable to produce a frequency distribution and bivariate analysis to see the relationship between the independent variable and the dependent variable. Where the statistical test used is the Chi-Square test and the alternative is the Fisher's Exact test. Conclusion: There is a relationship between the level of nurse knowledge, nurse attitudes, nurse skills and nurse compliance with Standard Operating Procedures in the Community Health Center Inpatient Room.